Shrinkage properties of steel fiber reinforced concrete- A review - Mohammad Abedi; Terje Kanstad; Stefan Jacobsen; Guomin Ji (Applications in Engineering Science, 2025)
Cracks induced by concrete shrinkage may allow corrosive agents to penetrate steel reinforced concrete and deteriorate the reinforcement. Adding randomly distributed steel fiber to concrete can reduce shrinkage and prevent the initiation of cracking, along with improving tensile strength and ductility. Autogenous shrinkage and drying shrinkage are the most important types of shrinkage in steel fiber reinforced concrete (SFRC). There is a general lack of knowledge related to the autogenous and drying shrinkage of SFRC. In the paper, the main factors that affect the autogenous shrinkage and drying shrinkage of SFRC are thoroughly examined through literature review. These factors include fiber volume, fiber geometry, curing method, water binder ratio (w/b), expansive agent, shrinkage mitigation, supplementary cementitious material (SCM), admixtures and hybridizing different fiber materials. It is concluded that increasing fiber volume up to some optimal volume, using expansive agents and shrinkage mitigation, as well as hybridizing different fibers, can reduce markedly the drying shrinkage. Furthermore, the water binder ratio, curing method and presence of silica fume, fly ash, and ground granulated blast furnace slag (GGBFS) influence shrinkage development in SFRC. In the last part, models predicting the autogenous and drying shrinkage of SFRC are discussed and new research is proposed.